2020
DOI: 10.1371/journal.pone.0238661
|View full text |Cite
|
Sign up to set email alerts
|

Volatile versus total intravenous anesthesia for 30-day mortality following non-cardiac surgery in patients with preoperative myocardial injury

Abstract: We evaluated whether volatile anesthetics can improve the postoperative outcomes of noncardiac surgery in patients with preoperative myocardial injury defined by the cardiac troponin elevation. From January 2010 to June 2018, 1254 adult patients with preoperative myocardial injury underwent non-cardiac surgery under general anesthesia and were enrolled in this study. Patients were stratified into following two groups according to anesthetic agents; 115 (9.2%) patients whose anesthesia was induced and maintaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…63 In 2019, Kwon et al 67 found that volatile anesthetics and TIVA exhibited equivalent effects in patients without preoperative myocardial injury in the observation of myocardial injury after noncardiac surgery. Later, Park et al 106 found that noncardiac surgery patients with preoperative myocardial injury and elevated cardiac troponin demonstrated significantly improved survival with intraoperative volatile anesthetics. However, this study was on volatile anesthetics and not specifically on the protective effects of desflurane, so we need further studies to confirm this beneficial effect of desflurane.…”
Section: Desfluranementioning
confidence: 99%
“…63 In 2019, Kwon et al 67 found that volatile anesthetics and TIVA exhibited equivalent effects in patients without preoperative myocardial injury in the observation of myocardial injury after noncardiac surgery. Later, Park et al 106 found that noncardiac surgery patients with preoperative myocardial injury and elevated cardiac troponin demonstrated significantly improved survival with intraoperative volatile anesthetics. However, this study was on volatile anesthetics and not specifically on the protective effects of desflurane, so we need further studies to confirm this beneficial effect of desflurane.…”
Section: Desfluranementioning
confidence: 99%
“…Nevertheless, the controversy persists regarding whether volatile anesthetics provides better outcomes for patients with preoperative myocardial injury during noncardiac surgery compared to total intravenous anesthesia. In a single center, retrospective cohort study of 1,254 patients with preoperative myocardial injury undergoing non-cardiac surgery, the researchers found the use of volatile anesthetics showed the significant survival improvement after non-cardiac surgery in patients with preoperative myocardial injury ( 51 ). However, a different study focusing on abdominal great vessel surgery did not yield positive results ( 52 ).…”
Section: Introductionmentioning
confidence: 99%